If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + -1) + ln(x + 1) = ln(x + 5) Reorder the terms: ln(-1 + x) + ln(x + 1) = ln(x + 5) (-1 * ln + x * ln) + ln(x + 1) = ln(x + 5) (-1ln + lnx) + ln(x + 1) = ln(x + 5) Reorder the terms: -1ln + lnx + ln(1 + x) = ln(x + 5) -1ln + lnx + (1 * ln + x * ln) = ln(x + 5) -1ln + lnx + (1ln + lnx) = ln(x + 5) Reorder the terms: -1ln + 1ln + lnx + lnx = ln(x + 5) Combine like terms: -1ln + 1ln = 0 0 + lnx + lnx = ln(x + 5) lnx + lnx = ln(x + 5) Combine like terms: lnx + lnx = 2lnx 2lnx = ln(x + 5) Reorder the terms: 2lnx = ln(5 + x) 2lnx = (5 * ln + x * ln) 2lnx = (5ln + lnx) Solving 2lnx = 5ln + lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-5ln' to each side of the equation. -5ln + 2lnx = 5ln + -5ln + lnx Combine like terms: 5ln + -5ln = 0 -5ln + 2lnx = 0 + lnx -5ln + 2lnx = lnx Add '-1lnx' to each side of the equation. -5ln + 2lnx + -1lnx = lnx + -1lnx Combine like terms: 2lnx + -1lnx = 1lnx -5ln + 1lnx = lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -5ln + 1lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-5 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5 + x)' equal to zero and attempt to solve: Simplifying -5 + x = 0 Solving -5 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + x = 0 + 5 x = 0 + 5 Combine like terms: 0 + 5 = 5 x = 5 Add '-1x' to each side of the equation. x + -1x = 5 + -1x Combine like terms: x + -1x = 0 0 = 5 + -1x Simplifying 0 = 5 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -x-(-8)=-12 | | 17=x+(2x+5) | | 4(2x+1)-7(x+4)=18 | | 3x+2(10-x)=20 | | -5(-p+6)=-2p-30 | | 30x+12x=6 | | 12=3j-4 | | x+2x+5x=16 | | 4(p+7q-13)= | | 7(k+4)-5=7+5k | | 3(p+4q-14)= | | 29=x+2x+(4x+1) | | 5y^2-125= | | 33-3n=-n-7(8n+3) | | 2(x+4)=3(x-7) | | x+4=3(x-7) | | 4x-9=3x+8 | | 2x-18=-8 | | 4x^3-44x^2+112x=0 | | 9x-5=5(x+1)+4x-10 | | 7x-1=7(x+8) | | -(1-8x)-1=-6+7x | | 16(n+7)=4(28+4n) | | 5x+1=2x-11 | | 7x+3=-3+3x+26 | | -0.3x^2+0.1x=-0.02 | | 5(x+5)+6=31 | | 2x+.666x=16 | | 6(3y-1)-3(2y)=14 | | 3-x=-4(8+2x) | | 48x^2-14x+1=0 | | y=3x^2+2x |